2013
DOI: 10.1104/pp.112.213231
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Transcriptional Network for Maize Defines Coexpression Modules      

Abstract: Here, we present a genome-wide overview of transcriptional circuits in the agriculturally significant crop species maize (Zea mays). We examined transcript abundance data at 50 developmental stages, from embryogenesis to senescence, for 34,876 gene models and classified genes into 24 robust coexpression modules. Modules were strongly associated with tissue types and related biological processes. Sixteen of the 24 modules (67%) have preferential transcript abundance within specific tissues. One-third of modules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 55 publications
3
64
0
Order By: Relevance
“…Tissue differentiation has generally been linked to deep transcriptome reorganizations compared to that associated with developmental stages or environmental conditions in plants including Arabidopsis (Ma et al, 2005) and maize (Downs et al, 2013). The survey of forest tree transcriptome studies presented in Table 2 is consistent with this observation.…”
Section: Tissue Comparison and Transcriptome Organizationsupporting
confidence: 58%
“…Tissue differentiation has generally been linked to deep transcriptome reorganizations compared to that associated with developmental stages or environmental conditions in plants including Arabidopsis (Ma et al, 2005) and maize (Downs et al, 2013). The survey of forest tree transcriptome studies presented in Table 2 is consistent with this observation.…”
Section: Tissue Comparison and Transcriptome Organizationsupporting
confidence: 58%
“…It also indicated that N‐responsive transcriptional analyses could differ markedly, even from time points only a few days apart. It is well established that gene expression changes greatly between tissues and across the development of multiple plants including Arabidopsis (Ma et al ., ; Schmid et al ., ), soya bean (Libault et al ., ), Medicago truncatula (Benedito et al ., ), rice (Jiao et al ., ; Wang et al ., ), barley (Druka et al ., ), bread wheat (Schreiber et al ., ) and maize (Downs et al ., ; Liseron‐Monfils et al ., ; Sekhon et al ., ). Our analysis that builds on this work has revealed responsive transcription is highly dynamic across the life cycle, and proper interpretation of expression data requires knowledge of this variation under steady‐state NO3 conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, there has been an upsurge in the number of studies reporting global co-expression networks of plants based on genome wide transcriptome data [14,15,16]. A number of tools namely ATTED-II [17], CressExpress [18], RiceArrayNet [19], OryzaExpress [20] and RiceFREND [21] based on co-expression networks are available that can be explored to identify novel genes, predict gene functions and characterize gene regulatory networks.…”
Section: Introductionmentioning
confidence: 99%
“…Implemented in R as a package, WGCNA provides a vast array of functions to detect, analyze and export individual and consensus modules from diverse but related microarray studies. WGCNA has been utilized to detect coexpression modules in Arabidopsis , rice, maize, soybean and poplar [14,24,25] and also across species [26]. …”
Section: Introductionmentioning
confidence: 99%